Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Guru Sd It Qoshrul Muhajirin - Abdul Qadir, Ramdan; Herdiyanti; Madyasari, Rina (Jurnal Ekonomi Bisnis dan Manajemen, 2025)
This study aims to analyze the impact of compensation and work discipline on teacher performance at SD IT Qoshrul Muhajirin. To achieve this objective, this study applies a quantitative method. The population involved in this study consists of 71 individuals. In determining the sample, this study applies a saturated sampling technique with a total sample of 71 individuals who are teachers at SD IT Qoshrul Muhajirin. The results of this study indicate that, partially, compensation has a positive impact on teacher performance, while work discipline also has a positive influence on teacher performance.